Learn ECG in a day : a systematic approach - Sajjan M. (Jaypee-Highlights, 2013)
Interpretation of electrocardiograph is an essential part of cardiovascular diangnosis. ECG is an important diagnostic tool in the diagnosis of cardiac as well as some metabolic problems. To read an ECG correctly, one has to be thorough with the basic knowledge of electromechanical system of the heart. It also requires a lot of imaginations and logic conclusions.